Redesigning Kidney Care for the Anthropocene: A New Framework for Planetary Health in Nephrology. (August 2022) - Rajan, Tasleem; Amin, Syed Obaid; Davis, Keefe; Finkle, Neil; Glick, Naomi; Kahlon, Bhavneet; Martinusen, Dan; Pederson, Kristen; Samanta, Ratna; Tarakji, Ahmad; Stigant, Caroline
Climate change is one of the greatest threats to human health in the 21st century. The human health impacts of climate change contribute to approximately 1 in 4 deaths worldwide. Health care itself is responsible for approximately 5% of annual global greenhouse gas (GHG) emissions. Canada is a recent signatory of the 26th United Nations Climate Change Conference (COP26) health agreement that is committed to developing low carbon and climate resilient health systems. Kidney care services have a substantial environmental impact and there is opportunity for the kidney care community to climate align clinical care. We introduce a framework of redesigned kidney care and describe examples of low carbon kidney disease management strategies to expand our duty of care to the environment which completes the triple bottom line of optimal patient outcomes and cost effectiveness in the Anthropocene.